The effect of mastery goal-complexes on mathematics grades and engagement: The case of Low-SES Peruvian students. (August 2022) - Benita, Moti; Matos, Lennia; Cerna, Yasmin
Abstract: Recent research anchored in achievement goal theory suggests mastery goals are more adaptive when endorsed for autonomous rather than controlled reasons. We report on two studies (N = 622) in which we explored whether the combined effects of goals and reasons on academic outcomes were different for a sample of low-SES youth than for other older higher-SES samples in the literature. Participants were low-SES high-school students in Lima, Peru. The results show that autonomous reasons for endorsing mastery goals positively predicted students' collective engagement and mathematics grades above the effect of mastery goals as such. Second, controlled reasons negatively predicted end-of-the year math grades. Finally, mastery goals' relations with mathematics grades and behavioral engagement were attenuated when endorsed for low autonomous reasons. The findings extend the knowledge on mastery goal-complexes and show they apply to low-SES students. Highlights: Mastery goals predict mathematics grades. Autonomous reasons predict emotional and cognitive engagement. Autonomous reasons moderated the relation of mastery goals with outcomes.